TRAINING ON PRODUCT DEVELOPMENT AND BRANDING STRATEGY FOR KAMPUNG MANDIRI SUSU SAPI PERAH - Hariani, Dina; Rahardian, Wildan Rizky; Utami, Indri Putri; Rahmaniyah, Nisa (LPPM Univ. Ibn Khaldun Bogor, 2024)
Bogor City has the potential for natural, cultural, and culinary tourism, including Thematic Tourism Villages. One of the villages that has the potential to be developed as a tourist destination in Bogor City is Kampung Mandiri, located in Kebon Pedes, Tanah Sareal District, which features a dairy farm in the middle of the city. This village is easily accessible from Bogor and Jakarta, with its main economy coming from livestock and culinary businesses. The community service activities aim to enhance the skills of farmers and brand Kampung Mandiri. The first training conducted was on Developing Dairy-Based Products, and the second was on Branding Strategies for Kampung Mandiri. These trainings were based on prior observations that the community in Kampung Mandiri lacked product variety and understanding of the importance of branding. As a result of the first training, participants learned to create dairy products such as dairy nuggets, milk candies, and milk mochi. In the second training on branding, Kampung Mandiri will use the logo KAMPUSS (Kampung Mandiri Susu Sapi Perah) as its identity and create an Instagram account for branding purposes. The training has proven to enhance the skills of farmers, members of the PKK (Family Welfare Program), and MSMEs in Kampung Mandiri, based on the results of pre-tests and post-tests conducted after the training.